2013
DOI: 10.3109/02703181.2013.825362
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Older Adult Care Transitions From Hospital to Home: A Participatory Action Research Project

Abstract: Using a participatory action research approach, community-based older adult service providers and university researchers partnered to explore older adult care transitions through the health care system, specifically from a hospital stay to home with rehabilitative services. Qualitative findings of transitioning home from both older adult and service provider perspective included three major themes: social support, communication, and adjusting to home and planning for the community. In addition, resources devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 1 publication
0
35
0
Order By: Relevance
“…Some explained how they were able to handle their decreased ability to perform daily activities by using adaptation strategies, such as dividing activities into smaller tasks, while others abstained from performing these activities. Using different strategies to adapt to new situations is well known from other studies (Aberg, Sidenvall, Hepworth, O'Reilly, & Lithell, 2005;Neiterman, Wodchis, & Bourgeault, 2015;Zakrajsek, Schuster, Guenther, & Lorentz, 2013). A study from 2005 revealed that elderly patients adopt different adaptation strategies in their everyday lives to avoid negative experiences due to their health condition (Aberg et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Some explained how they were able to handle their decreased ability to perform daily activities by using adaptation strategies, such as dividing activities into smaller tasks, while others abstained from performing these activities. Using different strategies to adapt to new situations is well known from other studies (Aberg, Sidenvall, Hepworth, O'Reilly, & Lithell, 2005;Neiterman, Wodchis, & Bourgeault, 2015;Zakrajsek, Schuster, Guenther, & Lorentz, 2013). A study from 2005 revealed that elderly patients adopt different adaptation strategies in their everyday lives to avoid negative experiences due to their health condition (Aberg et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The exploration and comparison of the meaning of loneliness among older adults living in different places such as nursing homes, their own homes, and public care homes will provide a more comprehensive description of the phenomenon of loneliness. To examine the effect of various interventions to reduce loneliness in older adults calls for participatory action research (Zakrajsek, Schuster, Guenther, & Lorenz, 2013) to involve the older adults in the research process.…”
Section: Implications For Practice Education and Researchmentioning
confidence: 99%
“…The participants in this study identified the importance of family and social support during the first 30 days after returning home from an inpatient stay. While the findings regarding relationships were similar to those of other studies (Wu & Lu, ; Zakrajsek et al, ), and participants reported a period of adjustment after returning home (Zakrajsek et al, ), participants in this study did not indicate a need for better communication with healthcare providers as was found previously (Zakrajsek et al, ). The participants also did not emphasise the role of (a) enhanced care and support during transitions; (b) improved patient education and self‐management support; or (c) multidisciplinary team management as identified in previous research focused on healthcare providers’ interventions to reduce re‐hospitalisation (Boutwell & Hwu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Only one study in the review focused on the role of the client during the first 30 days after hospitalisation. Using participatory action research, Zakrajsek, Schuster, Guenther, and Lorenz () identified three themes that are important in the immediate posthospital period. The themes included: (a) social support; (b) communication; and (c) adjusting to home and planning for living the community.…”
Section: Introductionmentioning
confidence: 99%